A comparative study of virus nucleic acid re-positive and non-re-positive patients infected with SARS-CoV-2 Delta variant strain in the Ningxia Hui Autonomous Region - Wang, Jing; Zhang, Shu-Xiang; Na, Jian-Rong; Zhang, Li-Ling; Zhang, Yin-Hao; Chu, Jiao-Jiao; Guo, Lei; Yan, Mei; Li, Yu-Ting; Zhou, Wei (Frontiers in Public Health, 2022)
Objective This study aimed to provide a basis for epidemic prevention and control measures as well as the management of re-positive personnel by analyzing and summarizing the characteristics of re-positive patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Delta variant infections discharged from a hospital in the Ningxia Hui Autonomous Region in 2021. Methods This case-control study included a total of 45 patients with Delta variant infections diagnosed in the Fourth People's Hospital of the Ningxia Hui Autonomous Region between October 17 and November 28, 2021. Based on the nucleic acid test results post-discharge, the patients were dichotomized into re-positive and non-re-positive groups. Based on the time of the first re-positive test, the re-positive group was further divided into <7 and ≥7 days groups to compare their clinical characteristics and explore the possible influencing factors of this re-positivity. Results Of the 45 total patients, 16 were re-positive (re-positivity rate: 35.6%), including four patients who were re-positive after 2 weeks (re-positivity rate: 8.8%). The median time of the first re-positive after discharge was 7 days (IQR: 14-3). The re-positive group was younger than the non-re-positive group (35 vs. 53, P < 0.05), had a higher proportion of patients who were not receiving antiviral therapy (56.2 vs. 17.2%, P < 0.05). The median CT value of nucleic acid in the re-positive group was considerably greater than that at admission (36.7 vs. 22.6 P < 0.05). The findings demonstrated that neutralizing antibody treatment significantly raised the average IgG antibody level in patients, particularly in those who had not received COVID-19 vaccine (P < 0.05). The median lowest nucleic acid CT value of the ≥7 days group during the re-positive period and the immunoglobulin G (IgG) antibody level at discharge were lower than those in the <7 days group (P < 0.05). When compared to the non-positive group, patients in the ≥7 days group had a higher median virus nucleic acid CT value (27.1 vs. 19.2, P < 0.05) and absolute number of lymphocytes at admission (1,360 vs. 952, P < 0.05), and a lower IgG antibody level at discharge (P < 0.05). Conclusions In conclusion, this study found that: (1) The re-positivity rate of SARS-CoV-2 Delta variant infection in this group was 35.6%, while the re-positivity rate was the same as that of the original strain 2 weeks after discharge (8.0%). (2) Young people, patients who did not use antiviral therapy or had low IgG antibody levels at discharge were more likely to have re-positive. And the CT value of nucleic acid at the time of initial infection was higher in re-positive group. We speculated that the higher the CT value of nucleic acid at the time of initial infection, the longer the intermittent shedding time of the virus. (3) Re-positive patients were asymptomatic. The median CT value of nucleic acid was > 35 at the re-positive time, and the close contacts were not detected as positive. The overall transmission risk of re-positive patients is low.